2x-y+3z=

Simple and best practice solution for 2x-y+3z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-y+3z= equation:


Simplifying
2x + -1y + 3z = 0

Solving
2x + -1y + 3z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'y' to each side of the equation.
2x + -1y + y + 3z = 0 + y

Combine like terms: -1y + y = 0
2x + 0 + 3z = 0 + y
2x + 3z = 0 + y
Remove the zero:
2x + 3z = y

Add '-3z' to each side of the equation.
2x + 3z + -3z = y + -3z

Combine like terms: 3z + -3z = 0
2x + 0 = y + -3z
2x = y + -3z

Divide each side by '2'.
x = 0.5y + -1.5z

Simplifying
x = 0.5y + -1.5z

See similar equations:

| 1-2x=5-6 | | 5/-12 | | -7y=-x+12 | | 1-((x-2)/3) | | 3x+-12=3x+-12 | | .333(3.14)r^2(8.5)=142 | | 9x^2-8x=-3 | | cosx-2sinx=1 | | x-1.08=2.96 | | 4y=-10+x | | 406.8184=2*3.14*136.89+2*3.14*11.7*h | | K-7k= | | (4w-8)+2w=64 | | X+-3=18 | | 12*7+908p=908 | | 0.1(100-x)=0.35x | | 3sin(2x)+3sinx=0 | | 10.1666667=a | | 742.61=2*3.14*256+2*3.14*16*h | | -6.4(4x+6)-2.1(2x-4)= | | 10.1666667= | | 9a-2b= | | 2m+1*-5= | | 0.7=0.861 | | (x*12)+x=9646 | | 7+5*8+78u=12y+4z | | -6.25=0.6c | | x+0.15=2500 | | 3(2n+5)=9(3n+7)+8 | | l+l+0.25l=135 | | -1.3g+1.9=11.1 | | 6(3s+7)=276 |

Equations solver categories